Co-regulation of ribosomal protein genes as an indicator of growth status: Comparative transcriptome analysis on axillary shoots and seeds in Arabidopsis - Tatematsu, Kiyoshi (Landes Bioscience, 2008)
Plant growth is regulated by internal and external cues using a limited number of genes coded in the genome. Comparative transcriptome analysis often provides an indication of which particular sets of genes are co-regulated in different physiological events. We have recently reported that protein synthesis-related genes were highly overrepresented in the genes upregulated during germination in Arabidopsis. In particular, these included ∼100 ribosomal protein (RP) genes. The promoters of these genes had a higher frequency of two cis elements, designated as Up1 and Up2. Up1 is almost identical to the target cis element of TCP transcription factors. We also found that a similar set of RP genes is upregulated during decapitation-induced axillary shoot outgrowth. Thus, Up1-mediated activation of RP genes appears to be a common mechanism for growth induction in axillary shoots and imbibed seed. Moreover, co-regulation of a large number of RP genes suggests that these genes are useful markers to monitor growth states for microarray analyses.